In vivo efficacy of alkaline peroxide tablets and mouthwashes on Candida albicans in patients with denture stomatitis - (:unkn) unknown (UNIV SAO PAULO FAC ODONTOLOGIA BAURU, 2010)
Objective: Effective cleaning of dentures is important for the maintenance of good oral hygiene for denture stomatitis patients. The in vivo efficacy of three different brands of alkaline peroxide tablets (Polident, Efferdent, and Fittydent) and two mouthwashes (CloSYS II and Corsodyl) to eliminate Candida albicans on dentures was evaluated in this in vivo study. Material and Methods: Ninety denture wearers with clinical evidence of denture stomatitis were randomly divided into 5 test groups and 1 control group. Each group was further divided into three subgroups in which the dentures were subjected to 15-, 30-, and 60-min disinfection procedures. The dentures of each test group were treated with one of the cleaners, while those of the control group were treated with distilled water. Swab samples from the palatal surfaces (2 cm x 2 cm template delimited area) of the upper dentures were obtained before and after 15, 30, and 60 min periods of cleaner use and examined mycologically. Results: The reduction in the number of colony-forming units (CFU) of C. albicans before, and after 15, 30, and 60 min of use of CloSYS II and Corsodyl was significantly greater than that of the control group (p<0.05). Moreover, there was no statistically significant difference (p>0.05) among Polident, Efferdent and the control group in any of the treatment periods. Dentures treated with Fittydent appeared to have a significantly greater reduction in the number of Candida spp. only after 60 min of treatment. Conclusions: The results of this study showed that the use of mouthwashes significantly reduced the number of microorganisms on dentures.
Keywords: Complete dentures; Denture cleansers; Denture stomatitis; Candida albicans; ORAL HYGIENE; CLEANSING AGENTS; SURFACES; CLEANERS; WEARERS; INVITRO; YEASTS; PLAQUE; PASTE